Targeting apoptosis pathways by natural compounds in cancer: Marine compounds as lead structures and chemical tools for cancer therapy - von Schwarzenberg, Karin; Vollmar, Angelika M. (Cancer letters, 2013)
Natural compounds derived from marine organisms have shown a wide variety of anti-tumor effects and a lot of attention has been drawn to further development of the isolated compounds. A vast quantity of individual chemical structures from different organisms has shown a variety of apoptosis inducing mechanisms in a variety of tumor cells. The bis-steroidal cephalostatin 1 for example, induces apoptosis via activation of caspases whereas the polyketide discodermolide inhibits cell growth by binding to and stabilizing microtubule and salisporamide A, the product of an actinobacterial strain, is an inhibitor of the proteasome. This great variety of mechanisms of action can help to overcome the multitude of resistances exhibited by different tumor specimens. Products from marine organisms and their synthetic derivates are therefore an important source for new therapeutics for single agent or combined therapy with other chemotherapeutics to support the struggle against cancer.